Neonatal outcome of suspected fetal distress cases (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Perinatal mortality is closely related to the early and accurate recognition of foetal distress. Objective of the study was to find out neonatal outcome in suspected fetal distress cases.Methods: This was a cross sectional study done in ShSMCH. Purposively 38 samples were taken in three weeks time and clinical state related to fetal distress and neonatal outcome of them were observed.Results: Fetal movement were less in 36.8% cases. Abnormal fetal heart rate were present in 89.4% cases and in 47.4% cases amniotic fluid was meconium stained. First minute Apgar score was low in 36.8% cases and 47.4% were admitted in paediatric ward. The clinical profile for diagnosis of fetal distress was not significantly associated with low apgar scores.Conclusion: There was very little appreciation for assumption of fetal distress clinically.J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 23-25